Exploring the Implementation and Outcomes of Virtual Simulation Technology in Recruitment Interview Teaching (Contemporary Education and Teaching Research, 2025)
Traditional recruitment interview teaching methods primarily rely on theoretical lectures and simple simulations, which have low fidelity in replicating real-life scenarios. This approach often fails to provide students with a profound understanding of the interview process, limited coping skills, and insignificant improvement in adaptability. In light of these issues, this paper aims to explore the application and effectiveness of virtual simulation technology in recruitment interview teaching. Virtual interview scenarios highly replicate real interview environments and can simulate various complex interview situations, allowing students to immerse themselves in the interview process. This method not only offers a more engaging learning experience but also significantly enhances student motivation. Additionally, it enables personalized teaching and precise assessment, allowing for timely understanding of student performance and assistance in improving key areas of growth. Finally, based on the actual outcomes, this study provides references for optimizing recruitment interview teaching methods and addressing existing problems.